Le ricette tecniche per l'arte negli autografi di Leonardo da Vinci: raccolta e edizione dei testi (Carte Romanze, 2020)
This contribution offers scholars Leonardo da Vinci’s collection of technical recipes for art that were dispersed among his numerous autographs. The recipes are edited from the autographs, and for some of them it has been possible to outline a textual tradition that shows also links with the vast contemporary tradition of technical texts in the Romance area.
Keywords: Leonardo da Vinci; technical recipes; arts; painting; textual tradition